2009
DOI: 10.1111/j.1365-2982.2009.01333.x
|View full text |Cite
|
Sign up to set email alerts
|

Irritable bowel syndrome is more frequent in patients hospitalized for ischaemic colitis: results of a case–control study

Abstract: It has been suspected that there is an epidemiological link between irritable bowel syndrome (IBS) and ischaemic colitis (IC). We performed a retrospective case-control study to compare the frequency of IBS in patients hospitalized for IC compared with that of patients with peptic ulcer bleeding. Cases were patients with a first episode of IC and controls were patients with a first episode of peptic ulcer bleeding, matched to cases for sex and 10-year age-class. Diagnosis of IBS was based on medical informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
1
8
0
2
Order By: Relevance
“…Previous studies have found that the incidence of IC was at least three time higher in IBS patients as compared to a matched control population[15-20]. With the exception of the report by Herve and colleagues[19], these studies used ICD-9 codes, with limited or no review of patient medical records for validation of case finding, potentially resulting in misclassification bias as highlighted above. On the other hand, the study by Herve et al included only hospitalized IC patients, and noted a lower prevalence of 1.6% of IBS in controls, compared to an expected rate of 4.7% in the general French population as reported by the authors, and may be indicative of inadequate matching[19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found that the incidence of IC was at least three time higher in IBS patients as compared to a matched control population[15-20]. With the exception of the report by Herve and colleagues[19], these studies used ICD-9 codes, with limited or no review of patient medical records for validation of case finding, potentially resulting in misclassification bias as highlighted above. On the other hand, the study by Herve et al included only hospitalized IC patients, and noted a lower prevalence of 1.6% of IBS in controls, compared to an expected rate of 4.7% in the general French population as reported by the authors, and may be indicative of inadequate matching[19].…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of the report by Herve and colleagues[19], these studies used ICD-9 codes, with limited or no review of patient medical records for validation of case finding, potentially resulting in misclassification bias as highlighted above. On the other hand, the study by Herve et al included only hospitalized IC patients, and noted a lower prevalence of 1.6% of IBS in controls, compared to an expected rate of 4.7% in the general French population as reported by the authors, and may be indicative of inadequate matching[19]. Our study did show a higher odds for IC in subjects with atherosclerotic diseases as highlighted in hospital-based manual record review studies [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…The adjudicated incidence rate of IC has been stable at approximately 1.0 cases/1000 patient-years, which is similar to the inherent background rate of IC in IBS patients that ranges from 0.40 cases/1000 patient-years to 1.79 cases/1000 patient-years [Cole et al 2004;Walker et al 2004; et al 2004]. Epidemiological studies have consistently demonstrated that IBS itself is an independent risk factor for IC, and have shown that patients with IBS have a two-to four-fold greater risk of developing IC than those without IBS Hervé et al 2009;Chang et al 2008]. Given the apparent increased background rate of IC among patients with IBS, the frequency of IC attributable to alosetron in the real-world, clinical practice setting remains difficult to determine.…”
Section: Discussionmentioning
confidence: 70%
“…Singh et al 2004]. Epidemiological studies have consistently demonstrated that IBS itself is an independent risk factor for IC, and have shown that patients with IBS have a two-to four-fold greater risk of developing IC than those without IBS [Walker et al 2004;Hervé et al 2009;Chang et al 2008]. Given the apparent increased background rate of IC among patients with IBS, the frequency of IC attributable to alosetron in the real-world, clinical practice setting remains difficult to determine.…”
Section: Discussionmentioning
confidence: 99%